1977
DOI: 10.1029/ja082i007p01061
|View full text |Cite
|
Sign up to set email alerts
|

Solar sources of the interplanetary magnetic field and solar wind

Abstract: Open magnetic field lines, those which extend from the solar photosphere to interplanetary space, are traced in the current‐free (potential field) approximation using measured photospheric fields as a boundary condition. It is found that (1) only a relatively small fraction of the photospheric area connects via open field lines to the interplanetary magnetic field; (2) those photospheric areas which do contribute open field lines lie beneath coronal holes and within the boundaries of the holes as projected ont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
97
0

Year Published

1979
1979
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(101 citation statements)
references
References 6 publications
1
97
0
Order By: Relevance
“…The wind speed is estimated at the source surface radius first. Solar wind speeds are known to correlate with the amount of field line divergence (Levine et al 1977;Wang & Sheeley 1990). Wang & Sheeley (1991) showed that such a correlation is plausible provided that the amount of Alfven wave energy flux is constant within open flux tubes.…”
Section: Stellar Windmentioning
confidence: 99%
“…The wind speed is estimated at the source surface radius first. Solar wind speeds are known to correlate with the amount of field line divergence (Levine et al 1977;Wang & Sheeley 1990). Wang & Sheeley (1991) showed that such a correlation is plausible provided that the amount of Alfven wave energy flux is constant within open flux tubes.…”
Section: Stellar Windmentioning
confidence: 99%
“…Crucially, a strong correlation was found between the average unsigned photospheric field strength in open-field regions and the solar wind speed at 1 AU. Nolte et al (1976) had demonstrated that the areas of large equatorial coronal holes are correlated with the maximum speeds of the associated solar wind streams, a pattern that Levine et al (1977) interpreted in terms of expanding flux tubes: high-speed winds originate from the centers of large holes because flux tube expansion is minimal there. This suggested that the solar wind flow could be treated in a manner similar to de Laval nozzle theory, in which con- Blue and yellow shading denote positive and negative polarities, respectively.…”
Section: Relationship Between Coronal Hole Structure and Solar Wind Smentioning
confidence: 99%
“…Studies in the 1970s using Skylab data suggested that regions with low areal expansion corresponded well with high-speed streams observed at Earth (Kopp & Holzer 1976;Levine et al 1977). Nearly two decades later, Wang and Sheeley (WS) established an empirical inverse relationship between the inecliptic solar wind speed (SWS) and the expansion rates of magnetic flux tubes (FTEs) defined as where B(phot) and B(ss) are the photospheric and the source surface magnetic fields at radii R e and R ss .…”
Section: Introductionmentioning
confidence: 99%